Konseling Kelompok Pendekatan Behavior Dengan Teknik Reframing Untuk Mengurangi Perilaku Agresif Peserta Didik - Pil Afia, Nowa; Pan Pangestie, Esty (Universitas Palangka Raya, 2024)
Aggressive behavior is an act of behavior that is carried out physically or verbally which is detrimental and carried out consciously by individuals to harm or injure other individuals. The purpose of this study was to determine the application of group counseling services using a behavioral approach with reframing techniques to reduce aggressive behavior in students. This research is a quantitative study using a pre-experimental design with the One-Group Pretest-Posttest Design type. Based on the results of the pre-test and post-test calculations, it can be seen that there is a significant difference in the experimental group, where the average percentage in the pre-test is 78% including the high category, then after being given group counseling with reframing techniques the post-test results of the five subjects have decreased to 50% in the low category. Based on the results of the Wilcoxon signed ranks test is 0.00 <0.05, then Ha is accepted and Ho is rejected. So it can be concluded that there is an average difference between the pre-test results and the post-test results, which means that there is an effect of using group counseling with reframing techniques to reduce verbal aggressive behavior. With this research, counseling teachers can apply reframing techniques in dealing with students who have problems, especially in the problem of verbal aggressive behavior.